(3GdEbJUGO GdEOGQjs - (3QVG UGMH(B, (3CHh MeOs; (3eDjO YHO GdMSjf GdaVd(B, s ((3YeGf(B:s (3OGQRgQGf ddfTQ hGdJhRjY(B,s, 2013)
(3GdEbJUGO GdEOGQj hYdGbJg HGdEbJUGO hGdEOGQI(B- (3JMdjd fXQjI GdWdH(B- (3gjcd GdCShGb eY GdJQcjR Ydi Shb GMJcGQ GdbdI(B- (3fXQjI GdJcGdja(B- (3fXQjI GdEfJGL(B- (3JMdjd fXQjI GdGQHGM(B- (3GdEfJGLjI hGdMhGaR(B- (3GdHYO GdEbJUGOj hEOGQI GdLhOI GdTGedI hGdEjRhs
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs; (3GdEbJUGOs; (3VHW GdLhOIs